PENGARUH POSISI MENERAN MIRING KIRI DENGAN KEJADIAN RUPTURE PERINEUM DI BPS SUGIYATI PETANAHAN - Dyah Puji Astuti; H Handoyo; Dewi Ayu Pangestika (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2015)
Bleeding of post partum it be came the first reason 40% mother died in Indonesia. The way of birth caused the second of bluding after atonia uteri, it happened nearly the first given birth, the happened of rupture perineum it be caused by the mother factor paritas and the distant of given birth, or the story of given birth, the mother psycology, the elacitas perineum, ekstraksi vacum, the given birth position, the heavy of baby body and episiotomi. The happening became rupture perineum, it could cause bluding and infection in the parturition time.This study is to know the influence of birth position towards the incident perineum ruptured during delivery babies in BPS Sugiyati Petanahan.This method of this study was quast exsperiment. The subject of these study were 43 women which had delivery babies. There were 22 women used half sit down position and 21 women used left side position. Data were collected by observation and analyzed by chi-square. This study show that (1) from 43 women given birth which they did given birth in BPS Sugiyati Petanahan , for the half sit down position was done by 22 women (51,16%), while the other21 women were used left side position (48,84%); (2) 26 women (60,47%) who had delivery babies had perineum ruptured in the left side positition many of 17 women (39,53%) and on the half sit down position many of 9 (20,93%), while the mother given birth did not had rupture many of 17 (39,53%) in the left side position they were 4 (9,30%) and the half sit down position they were 13 (30,23%). (3) statistical analyzed by chi square showed significant difference perineum ruptured incident betwen half sit down position and left side position p= 0,007 (p < 0,05). Keywords: birth position, delivery babies, left side position, half sit down position